2016
DOI: 10.1016/j.str.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Paring Down HIV Env: Design and Crystal Structure of a Stabilized Inner Domain of HIV-1 gp120 Displaying a Major ADCC Target of the A32 Region

Abstract: Summary Evidence supports a role of antibody-dependent cellular cytotoxicity (ADCC) toward transitional epitopes in the first and second constant (C1-C2) regions of gp120 (A32-like epitopes) in preventing HIV-1 infection and in vaccine induced protection. Here, we describe the first successful attempt at isolating the inner domain (ID) of gp120 as an independent molecule that encapsulates the A32-like region within a minimal structural unit of the HIV-1 Env. Through structure-based design, we developed ID2, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 54 publications
(115 citation statements)
references
References 60 publications
5
110
0
Order By: Relevance
“…infected individuals and to mediate potent ADCC responses (13,14,18,(20)(21)(22)(23)(24)(25)(26). Therefore, our results raise the intriguing possibility that histidine 375 present in the predominant strain replicating in Thailand might have contributed to the efficacy of the trial by spontaneously exposing epitopes recognized by ADCC-mediating antibodies elicited by the RV144 vaccine regimen.…”
Section: Figmentioning
confidence: 76%
See 1 more Smart Citation
“…infected individuals and to mediate potent ADCC responses (13,14,18,(20)(21)(22)(23)(24)(25)(26). Therefore, our results raise the intriguing possibility that histidine 375 present in the predominant strain replicating in Thailand might have contributed to the efficacy of the trial by spontaneously exposing epitopes recognized by ADCC-mediating antibodies elicited by the RV144 vaccine regimen.…”
Section: Figmentioning
confidence: 76%
“…Accordingly, we recently reported that the transition of Env to the CD4-bound conformation is required for efficient interactions with ADCC-mediating antibodies (14). We reported that the replacement of serine 375 by a tryptophan residue (S375W) enhanced the exposure of epitopes recognized by anti-cluster A antibodies, known to mediate potent ADCC responses (13,14,18,(20)(21)(22)(23)(24)(25)(26). Thus, the transition of Env from the unbound to the CD4-bound conformation appears to be a prerequisite for the exposure of inner-domain ADCC epitopes.…”
mentioning
confidence: 99%
“…Since it has been previously reported that the inner domain layers modulate recognition of gp120 by CD4i antibodies (15,16,30), we next examined the binding capacity of our panel of W69 gp120 variants to CD4i antibodies recognizing the coreceptor binding site (CoRBS; 17b and 48d) and anti-cluster A antibodies, known to be potent mediators of ADCC responses (A32, N5-i5, and N60-i3) (15,19,43,45,46). It was previously shown that CD4i antibodies preferentially recognize the CD4-triggered monomeric gp120, but they are still capable of binding to unliganded gp120 with roughly 10-to 20-fold lower affinities (15,18). Figure 3 and Table 2 show the binding of CoRBS and anti-cluster A antibodies to W69 mutant variants as quantified by immunoprecipitation and SPR, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, among these residues, W69 was recently shown to be important for efficient Env recognition by antibody-dependent cellular cytotoxicity (ADCC)-mediating anti-cluster A antibodies and also by sera from HIV-1-infected individuals (17)(18)(19)(20). Since W69 is located at the interface between layer 1 and layer 2 of the inner domain, we evaluated the contribution of hydrophobicity at this position to Env conformational changes.…”
mentioning
confidence: 99%
“…The conformation of the CD4i epitope has been captured in a truncated and stabilised gp120 innerdomain mini-protein which binds A32 and other CD4i specific mAbs [136]. This has been suggested to be a potential vaccine candidate for eliciting CD4i focused antibody responses but will first require an evaluation of the importance of off target killing of uninfected bystander cells to determine if this approach will be effective.…”
Section: Hiv Evasion and Subversion Of Fcγr-mediated Ab Functionsmentioning
confidence: 99%